A qualitative narrative policy framework? Examining the policy narratives of US campaign finance regulatory reform. (July 2016) - Gray, Garry; Jones, Michael D
In 2010, the narrative policy framework was introduced as a positivist, quantitative, and structuralist approach to the study of policy narratives. Deviating from this central tenet of the narrative policy framework, in this article we show that the framework is quite compatible with qualitative methods—and the various epistemologies associated with them. To demonstrate compatibility between qualitative methods and the Narrative Policy Framework, we apply classic qualitative criteria to an illustrative case examining policy narratives in US campaign finance reform. Drawing on elite interviews, we illuminate competing policy narratives rooted in distinct democratic values that exhibit variation in how victims and harm are defined, how blame is attributed to villains, what policy solutions are put forth, and policy narrative communication strategies. Our incorporation of qualitative methods within the narrative policy framework is critical for the framework's overall development as it provides opportunities for more detailed description, inductive forms of inquiry, and grounded theory development in policy areas where sample sizes, access, and salience may limit quantitative approaches.